The Oxford handbook of phenomenological psychopathology - Stanghellini, Giovanni; Raballo, Andrea; Broome, Matthew R.; Fernandez, Anthony Vincent; Fusar-Poli, Paolo; Rosfort, René (Oxford handbooks online, 2019)
For about one century the catalogue of books in phenomenological psychopathology has been tremendously rich in essays, but remarkably poor in handbooks. Even the cornerstone of our canon, Jaspers' General Psychopathology, originally written as a textbook, can hardly be given to a student as a basic reading. This makes teaching the fundamentals of the discipline difficult. Students ask for manualised knowledge expecting teachers to explain what must be done in a given circumstance. This Handbook is meant to fill these gaps. It includes a detailed, thorough and reader-friendly description of philosophical and clinical key-concepts and constructs, and of the contributions of leading figures of phenomenological psychopathology.